Waste and residue availability for advanced biofuel production in EU Member States. (June 2016) - Searle, Stephanie Y.; Malins, Christopher J.
Abstract: The EU is adopting policy measures to promote the use of advanced biofuels for transport made from sustainable sources including wastes and residues. As Member States prepare to implement these policy changes, they will need to understand if they have sufficient resource to meet an advanced biofuel target. This study assesses the availability of agricultural residues, forestry residues, and biogenic wastes that could potentially be used for advanced biofuel production in EU Member States at the present and projected to 2020 and 2030. This analysis incorporates specific information on agricultural, forestry, and waste production, management practices, and environmental risks in each Member State in order to model the amounts of residues needed to preserve soil quality and that are utilized in other industries; we exclude these quantities in order to determine the sustainable biomass potential that can be achieved without significant adverse impacts on the environment or biomass markets. We find that most EU Member States are likely to have more than enough sustainably available feedstock to meet the advanced biofuel requirement, and a majority may have more than 10 times the necessary amount. While this study does not assess economic viability of advanced biofuel production, from a resource perspective, the target appears to be achievable in most Member States. Some countries, including Austria, Cyprus, Denmark, Estonia, Ireland, Luxembourg, Malta, and Slovenia, may need to import either feedstock or advanced biofuel from neighboring countries to meet the target. Highlights: Sustainable availability of residues and wastes assessed. Quantities for soil protection and used in other industries estimated and excluded. Availability projected to increase in some countries and decrease in others to 2030. Most EU Member States have sufficient resource to meet an advanced biofuel target.